(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the theoretical and practical aspects of the Korean pronunciation system. Particular attention is paid to consonants and vowels, tense consonants, phonetic assimilation, intonation, and pronunciation rules. The study also analyzes the major pronunciation difficulties faced by learners of Korean as a foreign language and suggests possible solutions. Through various examples, the communicative importance of accurate pronunciation, its role in cultural adaptation, and effective methods of improving pronunciation skills are discussed. The findings of the study may serve as a theoretical basis for developing textbooks and methodological materials for Korean language learners.